CAPITAL GOVERNANCE IN SMALL INDUSTRIES IN WEST KWANYAR VILLAGE: A SHARIA FINANCIAL MANAGEMENT APPROACH - Nur Baiti, Siti; Taufiqur Rahman (Universitas Muhammadiyah Surabaya, 2024)
System, reduce risks, and promote sustainable economic growth by Islamic principles. Small industries in Kwanyar face several complex issues related to capital management, including a lack of transparency in financial transactions, the prohibition of usury, and profit sharing. This research aims to determine whether the principles of transparency and fairness in capital management, as stated in Sharia financial management, have been implemented. The research method used is a qualitative research method, which produces descriptive data in the form of written or spoken words from people and observable behavior, using a descriptive analysis approach. The results of this research show that the capital management process in the Small Industrial Business group in Kwanyar District, Bangkalan, is by Sharia financial management. This is evident from the application of the pecking order theory, a capital structure theory where financing starts from retained earnings (internal capital), and if insufficient, through debt or issuing new equity as a last resort (external). This aligns with Islamic law, which strictly prohibits usury in debt. In practice, business actors first use internal capital as the main capital and seek external financing when internal capital is insufficient